O03.2 Detection of glycosylated treponema pallidum proteins: relevance for diagnostic assays and importance for infection. (14th July 2019) - Gomez, Alloysius; Yip, Richard; Razavi, Morteza; Osbak, Kara; Houston, Simon; Kenyon, Chris; Leigh Anderson, N; Pearson, Terry; Cameron, Caroline
Abstract : Background: Current serology-based, treponemal-specific diagnostic tests detect antibodies reactive against T. pallidum molecules and cannot differentiate between past and current syphilis infections. Further, existing diagnostic tests for syphilis have non-optimal sensitivity and specificity and require expertise for test administration and interpretation. These limitations, combined with the rising number of syphilis infections, highlight the need for a reliable direct diagnostic assay to detect active syphilis. We sought to develop such an assay using immuno-mass spectrometry to detect T. pallidum proteins. Our results revealed that select T. pallidum proteins are glycosylated. Methods: We developed antibodies directed against proteotypic, surrogate peptides from six prioritized T. pallidum biomarker proteins. These antibodies were tested using a technology called Stable Isotope Standards and Capture by Anti-Peptide Antibodies (SISCAPA), which involves antibody enrichment of the peptide surrogates coupled with their identification by mass spectrometry. The anti-peptide antibodies were tested by SISCAPA and in immunoblots to detect T. pallidum proteins in urine from patients with clinically confirmed active syphilis. Results: Immunoblot analyses consistently identified T. pallidum proteins in urine samples from patients with syphilis. Initially, SISCAPA technology detected the surrogate peptides in only a fraction of the urine samples. However, deglycosylation of the proteins in the urine samples prior to SISCAPA analyses allowed successful identification of the T. pallidum biomarkers. Conclusion: This is the first report of protein glycosylation during T. pallidum infection. The results show sample deglycosylation prior to SISCAPA analysis improves peptide detection and enables use of a SISCAPA-based direct diagnostic test for accurately detecting active syphilis. Further, the results suggest a potential mechanism of immune evasion used during infection, that of masking T. pallidum proteins from the immune system by the addition of glycosyl groups. These findings increase our understanding of T. pallidum infection and will assist with development of a non-invasive, sensitive and specific assay for syphilis. Disclosure: No significant relationships.